Method for forming a hydrophilic surface on PS / DVB copolymer particles

By oxidizing, restore or hydrolysis of the polymer carrier material, and react with the multi -official compounds, the surface of the modified polymer carrier material, solve the problem of regulating hydrophilicity and capacity in existing technology, improve the stability of mechanical mechanical stability Sexual and chemical inertia enhances the separation effect of ion exchange chromatography.

CN113905821BActive Publication Date: 2025-01-28METROHM AG
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080038375.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-04-10
Filing Date
2020-04-07
Publication Date
2025-01-28
Estimated Expiration
2040-04-07

AI Technical Summary

Technical Problem

The prior art is difficult to independently adjust the hydrophilicity and capacity of the surface of polymer substrates, and the mechanical stability and chemical inertness of the particles are insufficient, which affects the separation effect of ion exchange chromatography.

Method used

By providing a polymer carriers formed by the achidic hydrocarbon compound with ethylenellin or allelene, a polymer carrier carrier material formed by the ethylene hydrocarbon compounds, oxidize, restore or hydrolysis treatment, generate a hydroxyl group, and react with multiple aggressive compounds to modify it to modify The surface of the polymerogle material material.

Benefits of technology

The hydrophilicity and capacity of the surface of the polymer carrier material is realized, the mechanical stability and chemical inertia of the particles are improved, and the separation performance of the ion exchange chromatography method is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113905821B_ABST
    Figure CN113905821B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for modifying a polymer support material for use as a stationary phase in an analytical or preparative separation process, the method comprising the steps of providing a polymer support material formed at least in part from an aromatic hydrocarbon compound comprising at least two vinyl or allyl substituents; generating hydroxyl groups on / in the polymer support material by means of a method comprising an oxidative treatment of the polymer support material and a subsequent reduction treatment or hydrolysis treatment of the reaction product; reacting the product from the previous step with a polyfunctional compound. The present invention also relates to a polymer support material prepared according to the method of the invention for use as a stationary phase in an analytical or preparative separation process, in particular a chromatographic process.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a method for modifying a polymer support material for use as a stationary phase in an analytical or preparative separation process, the method comprising the steps of providing a polymer support material formed at least in part from an aromatic hydrocarbon compound having at least two vinyl or allyl substituents; generating hydroxyl groups on / in the polymer support material by a method comprising an oxidative treatment of the polymer support material and a subsequent reduction treatment or hydrolysis treatment of the reaction product; reacting the product of the previous step with a polyfunctional compound. The present invention further relates to a polymer support material prepared by the method according to the invention for use as a stationary phase in an analytical or preparative separation process, in particular a chromatographic process.

[0002] Ion exchangers usually consist of particulate materials that carry on their surface an electric charge that enables them to retain ions. In the case of anion exchangers, these are usually cationic ammonium compounds, although phosphine and arsenic ions are also known. The exchanger group is a single cation. In purely electrostatic interactions, the retention time is determined by Coulomb's law. According to this, only the charge of the delayed anion should affect its retention time.

[0003] However, in ion chromatography in aqueous solution, other factors that affect the retention behavior can be identified, such as the hydration of anions and the hydration of exchanger groups. In addition, the polarizability of the ions involved and the weaker, secondary interactions between the analyte and the exchanger substrate also play a role. Since the hydrophilicity of the base polymer carrying the exchanger group also affects its hydration, the retention behavior of the ion exchanger can be changed by modifying the carrier material for the same exchanger group. The direct substituent of the cationic group also has an impact on the retention behavior.

[0004] The prior art already includes methods for adjusting the hydrophilicity of particles for use in ion exchange chromatography.Other desirable parameters, such as equilibrium capacity, high theoretical plate number or chemical inertness of the ion exchange material, are also selectively discussed.

[0005] In US20050181224, a crosslinked layer containing exchange groups is deposited on sulfonated hydrophilic support particles by cyclization of diepoxides and amines. With each cycle, the capacity of the ion exchanger increases. Hydrophilicity is essentially guaranteed. However, due to the alternating epoxy / amine chemistry, additional hydrophilicity independent of capacity cannot be obtained.

[0006] In EP 3248678, porous divinylbenzene particles are coated with modified polysaccharides (agarose reacted with glycidyl phenyl ether), and the modified polysaccharides are then cross-linked with a multifunctional cross-linking agent (e.g. ethylene glycol diglycidyl ether) to form macromolecules with hydroxyl groups on the surface. Thereafter, the substrate is fixed with diethylaminoethyl chloride hydrochloride to obtain the actual ion exchange groups. The present application also seeks hydrophilic ion exchange particles with increased stability (fracture strength). The substrate also proves to be more unstable due to the pure adsorption forces acting between the particles and the initial gel-like coating.

[0007] EP1217012 starts with a hydrophobic vinyl alcohol ester polymer. First, the contained ester is hydrolyzed in order to release the alcohol groups. The polymer becomes hydrophilic. The OH groups are reacted with diepoxides and then with amines to coat the substrate. The hydrophilicity can be further increased by subjecting the base polymer to a more extensive hydrolysis in a first step. However, this will lead to a loss of mechanical stability of the particles. Undesirable swelling behavior may occur.

[0008] In by et al. (J Sep Sci 2006, 29.940), attempts were made to optimize some of the mentioned parameters, such as theoretical scale number, pore size and surface expansion, by using a particle substrate of poly(vinyl acetate-co-divinylbenzene) of different composition. According to the printed paper, when the column loaded with the substrate is subjected to an increased flow rate, the increased amount of vinyl acetate - and therefore the increased amount of OH groups in the hydrolyzed particles - leads to a sharp increase in the reflux pressure. This undesirable reflux pressure is attributed to the lack of mechanical stability of the particles that deform during the separation process.

[0009] US5503933 discloses a hydrophilic coating covalently bonded to a hydrophobic surface and a method for its preparation. A compound comprising a hydrophobic region and a hydrophilic region including unsaturated groups is provided to form a coated surface. A hydrophobic surface with unsaturated groups is also provided. The molecules of the compound are adsorbed on the hydrophobic surface, and then the unsaturated groups in the hydrophobic region of the molecules of the compound are covalently bonded to the unsaturated groups on the hydrophobic surface by free radical reactions. In one embodiment, the hydrophilic coating can be covalently bonded to a polystyrene cross-linked with divinylbenzene. However, the resulting particles are only suitable for the separation of macromolecules. For use in other chromatographic techniques, particularly ion chromatography, the particles have an unsatisfactory theoretical plate number due to their large diameter. As the particle size decreases, the mechanical load bearing capacity of the macroporous material will be insufficient for the pressure generated in this chromatographic method.

[0010] The object of the present invention is to overcome the above disadvantages of the prior art. There is currently a lack of a method according to which a polymer substrate can be coated in such a way that the hydrophilicity of the polymer substrate surface can be adjusted independently of the oxygen content in the polymer core substrate and mechanically stable and robust particles are obtained. At the same time, the ion exchange substrate based thereon should be chemically largely inert and it should be possible to configure hydrophilicity and capacity or selectivity and capacity independently of each other.

[0011] This object is achieved by a method having the features of claim 1. It relates to a method for modifying a polymer support material for use as a stationary phase in an analytical or preparative separation method. The invention further relates to a polymer support material prepared according to the method according to the invention for use as a stationary phase in an analytical or preparative separation method, in particular a chromatographic method. The invention relates to a chromatographic column filled with a polymer support material according to the invention, a method for separating analytes using a polymer support material according to the invention, and the use of a polymer support material according to the invention for the analytical and preparative separation of analytes.

[0012] The method comprises the following steps: providing a polymer support material which is at least partially formed from an aromatic hydrocarbon compound having at least two vinyl or allyl substituents, preferably at least partially formed from a divinylbenzene monomer (step a); generating hydroxyl groups on / in the polymer support material by a method comprising the following steps: oxidative treatment of the polymer support material (step b.1); subsequent reduction or hydrolysis treatment of the reaction product of step b.1 (step b.2); optionally: reacting the product of step b.2 with a polyfunctional compound, in particular with a compound having at least one first functional group reactive with a hydroxyl group, preferably a halogen group, and at least one second functional group reactive with an amine and / or a hydroxyl group, preferably an epoxy group (step c).

[0013] It goes without saying that the functional groups reactive with amines can react with or simultaneously with other organic element compounds of main group 5, ie with arsine or phosphine.

[0014] As will be explained further below, in particular with regard to the method according to the invention, the steps according to the invention have an influence on the oxygen content at the surface of the polymeric support material. Thus, the hydrophilicity of the surface of the polymeric support material is independent of the oxygen content in the polymeric support core matrix.

[0015] The polymer support material provided in step a. is typically provided as particles, preferably as spherical particles, particularly preferably as spherical particles with an average particle size (median) of 1 to 50 μm, even more preferably with an average particle size of 2 to 25 μm, particularly preferably with an average particle size of 3 to 9 μm. However, other polymer support materials are also conceivable, in particular polymer support materials in the form of films or monoliths.

[0016] The oxygen content of the surface of the polymer support material is increased by initial oxidation and reduction or hydrolysis. The modification can also generate oxygen atoms on / in the core polymer support material that does not have a detectable oxygen content. The increased oxygen content affects the nature and performance of secondary interactions, in particular the hydrophilicity of the resulting polymer support material. In addition, by a series of steps after the initial oxidation and reduction / hydrolysis, the capacity can be adjusted independently of the oxygen content at the surface.

[0017] The surface of a polymer support material or polymer support material surface here particularly means the outer surface of the polymer support material structure that can be in contact with the solution and the layer of 1 to 30 nm next to the outer surface, wherein the outer surface that can be in contact with the solution can be located partly on the microstructure of the porous structure, for example. In particular, it means the outer surface of the polymer support material particles of a porous or non-porous structure that can be in contact with the solution.

[0018] The covalent bond between the polymer carrier material and the coating makes an initial contribution to chemical and mechanical stability. This is contrary to the situation of the ion exchanger based on latex, in which the latex particles and therefore the exchanger groups are maintained to the substrate purely by electrostatic interaction. Due to the covalent bond, high chemical inertness is also guaranteed. The second contribution to mechanical stability is made by the following fact: the core polymer carrier material is at least partially formed by an aromatic hydrocarbon compound with at least two vinyl or allyl substituents, preferably at least partially by divinylbenzene monomers. The stability of this core polymer carrier material is not affected by steps b.1 and b.2. The core polymer carrier material is preferably monodisperse.

[0019] Step c, i.e. the reaction of the product of step b.2. with a polyfunctional compound, in particular a compound having at least one first functional group reactive with a hydroxyl group and at least one second functional group reactive with an amine and / or a hydroxyl group, is optional. If this step is omitted, the particles are suitable, for example, for size exclusion chromatography.

[0020] In particular, the preparation of ion exchange materials for anion exchange chromatography or cation exchange chromatography based on the modified polymer support material according to the present invention is described below. However, the use of the particles is by no means limited to this. The particles can also be used for other analytical and preparative separation methods, such as other adsorption chromatography methods, HILIC chromatography (hydrophilic interaction liquid chromatography), reversed phase chromatography, solid phase extraction, etc.

[0021] In a preferred embodiment, the method comprises steps a, b and c as described above, and an additional step after step c, i.e., performing multiple coating cycles (step d). A single coating cycle, step d, comprises: introducing or generating hydroxyl groups by reacting a second functional group reactive with amine and / or hydroxyl groups, preferably an epoxy group introduced in step c, with a polyfunctional compound having hydroxyl groups, in particular with a polyol, or by hydrolysis or a combination thereof (step d.1); and reacting the product of step d.1 with a polyfunctional compound, in particular with a compound having at least one first functional group reactive with hydroxyl groups, preferably a halogen group, and at least one second functional group reactive with amine and / or hydroxyl groups, preferably an epoxy group (step d.2). The number of coating cycles is 0 to 20.

[0022] If the number of coating cycles is at least 2, the introduction or generation of hydroxyl groups from the first repetition onwards is obviously no longer of interest, or at least no longer exclusively of interest, to the functional groups introduced in step c, but rather mainly to the corresponding functional groups introduced in step d.2. This is particularly true if the conditions are chosen such that when the first coating cycle is carried out in step d.1, the second functional group from step c is essentially completely reacted.

[0023] By increasing the number of coating cycles, the oxygen content at the surface of the polymer support material can be further increased, and the hydrophilicity of the ion exchange material based on the polymer support material can be increased. By selecting an appropriate degree of hydrophilicity, the interaction of the ion exchange material with highly hydrated ions (e.g., fluoride ions) can be enhanced, and the interaction with too weakly hydrated ions (e.g., bromate, nitrate, chlorate) can be reduced. In this way, for example, the retention order of bromate and chloride can be affected so that bromate appears quantitatively before chloride in the chromatogram. In addition, it can be ensured that fluoride is separated from the injection peak, and particularly when a carbonate eluent is used.

[0024] Furthermore, by the method according to the invention, for seven standard anions (fluoride, chloride, nitrite, bromide, nitrate, phosphate and sulfate) with high signal symmetry (asymmetry <1.5), ion exchange materials with plate numbers of >50,000 TP / m theoretical plates per column meter can be obtained. In a chromatogram with a generally short total chromatography time, all of the above ions appear as baselines separated from one another.

[0025] The advantage of the high stability of the particles is particularly evident when a column filled with the polymer support material obtained by the above method is subjected to a pressure flow test. In this stress test, the pressure development in the column is determined as a function of a continuously increasing flow rate. In the column according to the invention, the pressure depends linearly on the flow rate. This is in contrast to the results obtained with conventional columns filled with a hydrophilic pDVB substrate with a high vinyl acetate content. For conventional columns, the pressure increases more than linearly as a function of the flow rate. For example, a hyperbolic slope of the function can be obtained. This is shown, for example, by the example cited at the beginning. et al. (J Sep Sci 2006, 29, 940).

[0026] The performance of the columns according to the invention after stress testing was also better than that of conventional columns. In one aspect, the columns exhibited only a small increase in pressure drop over the entire column after stress testing compared to conventional columns. In addition, during load testing on the columns according to the invention, the number of theoretical bottoms was reduced to 100% compared to the case of conventional columns ( et al., J Sep Sci 2006, 29, 940). Maintaining the pressure ratio and plate number enables efficient high performance separation methods even when high flow rates are used.

[0027] The method may then further comprise a step e of introducing ion exchange groups on the reaction product of step c or d.2. By step e, an ion exchange material is prepared from a polymer support material that achieves the advantages associated with a polymer support material. In the ion exchange material according to the invention, hydrophilicity and capacity or selectivity and capacity are independently adjustable. The ion exchange material according to the invention also has a large theoretical scale.

[0028] Ion exchange groups are understood to be charged groups on the surface of the polymeric support material, in particular charged amine, arsenic or phosphine groups.

[0029] For polymeric support materials formed at least in part from aromatic hydrocarbon compounds having at least two vinyl or allyl substituents, it is understood in the context of the present invention that the polymeric support material can be prepared by polymerization of at least an aromatic hydrocarbon compound having at least two vinyl or allyl substituents. Preferably, the polymeric support material is formed by polymerization with divinylbenzene. However, reactions with trivinylbenzene and divinylnaphthalene and equivalent compounds known to those skilled in the art are also conceivable.

[0030] The method may be characterized in that the polymer support material formed at least in part by an aromatic hydrocarbon compound having at least two vinyl or allyl substituents in step a is additionally formed in part by a monomer selected from ethylvinylbenzene, vinyl acetate, styrene, and combinations thereof. In this regard, the proportion of aromatic hydrocarbon compounds having at least two vinyl or allyl substituents is preferably at least 50% by weight. For example, the polymer support material in step a may contain at least 50% by weight of divinylbenzene units. Such a polymer support material has advantageous properties with respect to the pore structure, in particular having a large number of available double bonds for subsequent surface modification.

[0031] The method can be characterized in that the oxidative treatment in step b.1 is a treatment with a peracid preferably selected from meta-chloroperbenzoic acid (m-CPBA), performic acid, peracetic acid, peroxytrifluoroacetic acid, a treatment with KMnO4, a treatment with an oxygen plasma, or a combination thereof. Exposure of the polymer to the peracid oxidizes any double bonds present and makes them available for subsequent reduction or hydrolysis. It goes without saying that this effect can in principle also be achieved by other oxidation methods known to those skilled in the art, for example by ozonolysis.

[0032] It is particularly preferred if a peracid is used in step b.1. The advantage of a peracid is that higher oxygen contents can be achieved than, for example, a plasma treatment. With oxygen plasma an oxygen content of 2.0% can be achieved, whereas, for example, with mCPBA an oxygen content of 3.2% can be achieved, which can be measured by elemental analysis. If a peracid is used, it can be added to the polymer in the form of a suspension or formed in situ from acid and hydrogen peroxide. Preferably, the m-CPBA is added to a suspended core polymer support material, for example a PS / DVB polymer support material, since this is uncomplicated for processing as a solid.

[0033] In a preferred embodiment, the reduction treatment of the reaction product from the oxidation step b.1 is carried out in step b.2 using a reagent for reducing polar bonds, preferably a metal hydride. This can be, for example, NaBH4, BH3, LAH, NaH, CaH. The use of hydrides has the advantage that dissolved reagents can penetrate into the pores of the particles. For example, it is impossible to use palladium on activated carbon. Compared with hydrolysis with hydrochloric acid, which can convert epoxides into hydroxylenes (see Example 3), reduction with metal hydrides can also convert carbonyls and carboxyls into hydroxylenes. Reduction converts the formed oxidation product into alcohol. Preferably, lithium aluminum hydride in diethyl ether is used. In one embodiment, a polymer suspension of 1% to 20% weight / volume in dry diethyl ether to which 5% to 100% weight / weight of the dry weight of the polymer is added is provided. Particularly preferred is a polymer suspension of 5% to 15% weight / volume in dry diethyl ether to which 5% to 20% weight / weight of the dry weight of the polymer is added. The temperature can be selected to be 25° C.-70° C., particularly preferably the boiling temperature of diethyl ether, and the reaction time to be 1 min to 72 h, particularly preferably 3 h to 48 h.

[0034] The OH groups generated on the surface of the polymer support by the process described above are now available in sufficient number for the modification in step c. As an alternative to reducing conditions, hydrolytic conditions can also be chosen.

[0035] The reaction product of step b.2 is reacted with a polyfunctional compound, in particular with a compound having at least one first functional group reactive with a hydroxyl group, preferably a halogen group, and at least one second functional group reactive with an amine and / or a hydroxyl group, preferably an epoxy group.

[0036] The first functional group that can react with hydroxyl groups can be a structure that can be attacked by nucleophilic OH groups or amine groups, such as halogenated hydrocarbons, epoxides, toluene sulfonates, dimethyl sulfide, or mixtures thereof. The second functional group that can react with amines and / or hydroxyl groups can be, for example, epoxides. Preferably, the multifunctional compound in step c is epichlorohydrin (ECH). For example, the substrate can be suspended in epichlorohydrin (preferably 5%-30% weight / volume solids in ECH, more preferably 10%-20% weight / volume solids in ECH). Then it can react with a base, such as with an alkali metal hydroxide and an alkaline earth metal hydroxide aqueous solution. For this purpose, an aqueous solution of NaOH and KOH, particularly preferably 10%-50% weight / weight NaOH with a ratio of ECH:NaOH (aqueous solution) = 1: (0.1-10) has been shown to be suitable. Particularly preferably, a quaternary ammonium salt is used as a phase transfer catalyst for the reaction. Alternatively, the substrate suspended in ECH can react with a quaternary ammonium hydroxide. It has been found that tetramethylammonium hydroxide is suitable for this purpose. Preferably, the same amount of dimethyl sulfoxide (DMSO) as ECH is added to the suspension of the polymer in ECH prepared above, and preferably 1 to 10 mmol of tetramethylammonium hydroxide in concentrated aqueous solution, more preferably 2 to 5 mmol of tetramethylammonium hydroxide (aqueous solution) are added per gram of polymer used.

[0037] However, the multifunctional compound used in step c comprising at least one first functional group reactive with hydroxyl groups and at least one second functional group reactive with amine and / or hydroxyl groups may also be a spacer molecule.

[0038] In the context of the present application, a spacer molecule (referred to as spacer) means a molecule with at least two functional groups mentioned above, which ensures that at least 3 atoms, preferably 3 to 20 atoms are spaced between the surface of the modified polymer support material and the ion exchange group to be introduced. In the finished ion exchange material, the spacer molecule is combined with the modified polymer support material on the one hand, and combined with the exchanger group on the other hand. The functional group of the spacer molecule can be a structure that can be attacked by nucleophilic OH groups or amine groups, such as halogenated hydrocarbons, epoxides, toluene sulfonates, methyl sulfide or their mixtures. The spacer atom can be a carbon chain but can also include heteroatoms, such as ether groups or thioethers. The spacer molecule provides the interval between the substrate and the ion exchange group. The function of the spacer is to prevent ions from interacting with the substrate. This offsets the unwanted peak broadening in the chromatogram. Due to its higher hydrophilicity, preferably there is a spacer carbon chain with an ether group. Particularly preferably, the spacer has a glycidyl group that can react with amines, phosphine, arsenic and / or hydroxyl groups. Particularly preferred is the spacer molecule 1,4-butanediol diglycidyl ether.

[0039] When the hydroxyl group is introduced in step d.1 by reaction of the second functional group introduced by reaction with a polyfunctional compound containing a hydroxyl group in step c (or optionally in step d.2), preferably a diol is used. Particularly preferred is butanediol. The diol can be used as a solvent and reactant, and the reaction can be carried out at elevated temperatures under base catalysis. Particularly preferred is 0.1-1 mol / L KOH at 60°C-160°C for 1-48h. Most preferably, the temperature is 100°C-130°C and the reaction time is 3-36h. By adding this compound, the epoxide previously bound to the substrate is converted into a chain containing an OH group.

[0040] In one embodiment, the polyfunctional compound with at least one first functional group reactive with hydroxyl groups and at least one second functional group reactive with amine and / or hydroxyl groups used in step d.2 is epihalohydrin, preferably epichlorohydrin. In this regard, the carrier polymer particles can be first suspended in epichlorohydrin (preferably: 5%-30% weight / volume solid in ECH, more preferably 10%-30% weight / volume solid in ECH). Thereafter, the suspension can react with a base, for example, with an aqueous solution of an alkali metal hydroxide or an alkaline earth metal hydroxide. For this purpose, an aqueous solution of NaOH and KOH, particularly preferably with a ratio of ECH:NaOH (aqueous solution) = 1: (0.1-10) 10%-50% weight / weight NaOH has been shown to be suitable. Particularly preferably, a quaternary ammonium salt is used as a phase transfer catalyst to react.

[0041] However, a spacer molecule may alternatively be used in step d.2. It is particularly preferred that, if a spacer molecule is used, it is used at least in the last execution of the coating cycle in step d.2.

[0042] A preferred feature of the invention is that steps d.1 and d.2, which together are also referred to as coating cycles, can be repeated. The number of coating cycles may be 0 to 20, preferably 0 to 10. However, it is preferred that the number of coating cycles is 0 to 5, more preferably 1 to 3.

[0043] The hydrophilicity of the polymer support material increases with each cycle. By selecting an appropriate number of cycles, the hydrophilicity of the mixture to be separated can be optimally adjusted. Specifically, by selecting an appropriate degree of hydrophilicity, the hydrophilic interaction of the substrate with strongly hydrated ions (e.g., fluoride ions) can be enhanced, and the interaction with weakly hydrated ions (e.g., bromate, nitrate, chlorate) can be reduced. This can affect the retention order. The generation of each layer also reduces the secondary interaction between polarizable ions such as chlorate or bromate on the one hand and the substrate on the other hand. The tailing of the signal peak observed due to this secondary interaction is significantly reduced, so that even polarizable ions are eluted symmetrically. The total capacity of the exchange material is reduced.

[0044] In a preferred embodiment, a spacer molecule, in particular a diepoxide, preferably butanediol diglycidyl ether, is used as a polyfunctional compound in step d.2 in the final execution of the coating cycle d. The advantages of the spacer molecule have been described above in conjunction with step c. The reaction of the spacer molecule is preferably carried out under the condition that a polar solvent, particularly preferably DMSO in a volume ratio of 1: (0.1-5) relative to diglycidyl ether, more preferably in a ratio of 1: (0.5-1.5) is added to the reaction mixture. It is also preferred to use a quaternary ammonium salt as a phase transfer catalyst, particularly preferably tetrabutylammonium bromide in a concentration range of preferably 1-100 mmol / L, particularly preferably 10-50 mmol / L based on the total volume of the reaction mixture as a phase transfer catalyst. Alkali metal hydroxides and carbonates and alkaline earth metal hydroxides and carbonates can be used as bases, preferably aqueous solutions of NaOH and KOH, particularly preferably NaOH in a concentration range of 0.1-5 mol / L, most preferably in a concentration range of 0.1-1 mol / L as a base. The volume ratio relative to diglycidyl ether is 1:(0.1-5), preferably 1:(0.5-1.5). The preferred reaction temperature is 0°C-50°C, particularly preferably 20°C-30°C, and the preferred reaction time is 2-40h, particularly preferably 15-25h.

[0045] In a preferred embodiment, the ion exchange group is introduced by reacting the compound of step c or d.2 with an organic element compound of the 5th main group, preferably an amine, particularly preferably a tertiary amine. However, the ion exchange group may contain a phosphine or an arsenide instead of an amine. It has been shown that compounds containing amines with 1 to 3 organic groups of 1 to 10 C per group, which also include cyclic compounds, are particularly suitable. Cyclic compounds may have substituents. Examples of suitable compounds include nitrogen-containing heterocycles, such as pyridine, monosubstituted alkylpyrrolidine, monosubstituted alkylpiperidine or disubstituted alkylpiperazine with or without hydrocarbon or hydroxyl substituents. The hydrocarbon group of the amine compound may also have heteroatoms, such as oxygen or sulfur atoms, or other substituents.

[0046] However, it is also possible to consider introducing compounds suitable for cation exchange chromatography or HILIC methods. Suitable cationic functional groups include sulfonic acid, carboxylic acid, or a combination thereof. Preferably, the compound to be introduced may also have multiple functional groups, such as when introducing amino acids.

[0047] For example, to produce cation exchange centers, the polymer epoxidized in the previous step can be suspended in a mixture of water and a polar solvent, preferably DMSO, and the preferred amine can be added. The preferred reaction time is 0.5 to 48 h at a preferred temperature of 20° C.-70° C.

[0048] Preferably, step e of introducing the ion exchange groups is followed by a further step f comprising heating the polymer support material provided with ion exchange groups in an alkaline solution. This allows the selectivity and capacity of the ion exchange material from the previous step to be adjusted. This treatment is referred to below as elimination, and specifically comprises heating the particles provided with exchange groups in an alkaline aqueous solution, particularly preferably in an aqueous solution of an alkali metal hydroxide or carbonate or an alkaline earth metal hydroxide or carbonate, for example in a sodium hydroxide solution. The preferred concentration range of NaOH is in the range of 0.1 to 5 mol / L alkali, and particularly preferably 0.2 to 2 mol / L alkali. The reaction temperature may be 20°C-100°C, particularly preferably 90°C-100°C, and the treatment time is 0.1-150h, particularly preferably 2-6h.

[0049] The elimination step changes the relative strength of the interaction of the substrate with the individual ions. In particular, the secondary interaction with the polarizable analyte can be reduced. The tailing of the signal peak observed due to this secondary interaction is reduced, so that the polarizable ions are also eluted symmetrically. At the same time, the electrostatic interaction capacity of the column is also reduced after elimination, and the overall capacity of the ion exchange material is reduced.

[0050] Another aspect of the invention relates to a polymer support material for use as a stationary phase in analytical or preparative separation methods, in particular chromatographic methods, obtainable by a process comprising the steps as described above, at least steps a, b and c.

[0051] Another aspect of the invention relates to a polymer support material for use as a stationary phase in an analytical or preparative separation method, in particular a chromatographic method, which can be obtained by a method comprising the steps as described above, at least steps a and b, preferably at least steps a and b and c, wherein the polymer support material provided in step a is hydrophobic and microporous or mesoporous. By hydrophobic, it is understood that the polymer support material is non-polar, i.e., has no monomer units with a dipole moment> 0.2D. By microporous or mesoporous, it is understood that the polymer support material has an average pore size of at most 50 nm.

[0052] When the method comprises at least steps a, b, c and e, another aspect of the invention relates to a modified polymeric support material for use as a stationary phase in ion exchange chromatography.

[0053] The modified polymeric support materials obtainable in this way are characterized by

[0054] - starting from the value of the maximum O content, in each case a difference of at least 20%, preferably a difference of at least 50%, particularly preferably a difference of 100% is detectable by means of X-ray photoelectron spectroscopy XPS in a section through the polymeric carrier material;

[0055] - oxygen-containing groups are covalently bonded to the core polymer carrier material;

[0056] The polymer support material is mechanically stable, so that the pressure drop across the column packed with the polymer support material increases only linearly as a function of increasing flow rate;

[0057] - The polymeric carrier material carries no charge at neutral pH;

[0058] The polymer support material has a nitrogen content of less than 2%.

[0059] In particular, the modified polymer support material has a higher oxygen content at the surface than in the core. The modified polymer support material obtained by this method is also chemically inert to a large extent. The polymer support material thus obtained is adjustable because it can have a more or less oxygen-containing surface. Due to its structure and surface properties, the material is particularly suitable for use as a stationary phase in analytical or preparative separation methods. In particular, the substrate is suitable for further processing into a particulate ion exchange material prepared by the method described above, which is also part of the present invention. However, the polymer support material can also be further processed for other adsorption chromatography methods, HILIC methods, reversed phase chromatography, solid phase extraction, etc. Due to microporosity or mesoporosity, the modified polymer support material is suitable for producing columns with a large number of theoretical plates and correspondingly good separation performance, because microporous and mesoporous particles are mechanically stable even at small diameters, and the diffusion path can therefore be set shorter.

[0060] Another aspect of the invention relates to a modified polymeric support material according to the invention for use as a stationary phase in ion exchange chromatography, obtainable by a process comprising the steps described above, wherein according to step e, ion exchange groups are additionally introduced into the polymeric support material.

[0061] The ion exchange materials obtainable in this way can be characterized by

[0062] - starting from the value of the maximum O content, in each case a difference of at least 20%, preferably a difference of at least 50%, particularly preferably a difference of 100% is detectable by means of X-ray photoelectron spectroscopy XPS in a section through the polymeric carrier material;

[0063] - oxygen-containing groups are covalently bonded to the core polymer carrier material;

[0064] - the ion exchange material is mechanically stable, so that the pressure drop in a column packed with the polymer support material increases only linearly as a function of increasing flow rate;

[0065] - the ion exchange material is not based on a modification by means of an epoxide-amine reaction, except for the introduced ion exchange groups, which are possibly detectable by Hofmann elimination;

[0066] - Optionally, the ion exchange material has a plate number of >50,000 TP / m;

[0067] - Optionally, selectivity and capacity are additionally adjustable using elimination step f.

[0068] In particular, the ion exchange material has a higher oxygen content at the surface than in the core. For example, the surface of the modified polymer support material prepared by the method according to the invention up to and including step c has an oxygen content that is 50%, preferably 60% higher, based on the value of the maximum O content, than the inner particle area detectable by XPS measurement.

[0069] The advantage of the ion exchange material according to the present invention is that hydrophilicity and capacity or selectivity and capacity can be configured in a separate step, i.e. independently of each other. The ion exchange material prepared by the method according to the present invention only shows weak secondary interactions with polarizable ions and increases the retention time of strongly hydrated ions. Columns filled with hydrophilized ion exchange substrates show the desired selectivity. The material does not swell and shows favorable properties in stress tests. Particularly efficient columns can be filled with ion exchange materials.

[0070] The polymeric support material as described above is suitable as the stationary phase in the ion chromatography method, particularly for the stationary phase in the chromatography method for separating standard ions fluorine ion, chloride ion, nitrite, bromide ion, nitrate, phosphate and sulfate.The high ion exchange capacity of post is particularly necessary for separating little, singly charged ions or doubly charged ions.On the contrary, it is undesirable to transfer by convection or the perfusion mass of the analyte solution realized by macroporous structure.Macroporous structure is also often relevant to poor mechanical load bearing capacity.

[0071] The present invention also relates to a modified polymeric support material as described above, wherein the polymeric support material provided in step a consists essentially entirely of monomeric units selected from the group consisting of:

[0072] - monomer units derived from aromatic hydrocarbon compounds having at least two vinyl or allyl substituents, preferably from divinylbenzene;

[0073] - monomer units derived from ethylvinylbenzene;

[0074] - monomer units derived from styrene;

[0075] -A combination of these.

[0076] By "essentially completely built up" is understood here that the total proportion of the monomer units listed in the polymer carrier material provided in step a is at least 95% by weight, preferably at least 98% by weight, particularly preferably at least 99% by weight. In other words, the monomer units can be derived essentially completely from compounds that do not contain oxygen atoms, in order to obtain a hydrophobic particle core.

[0077] Another aspect of the present invention relates to a modified polymer support material as described above, wherein the polymer support material provided in step a has an average pore radius of 1 to 50 nm, preferably 2 to 25 nm, more preferably 2 to 10 nm, measurable by nitrogen adsorption in the BJH model. The measurement is performed as described in Example 5 below.

[0078] Another aspect of the present invention relates to a modified polymer support material as described above, wherein the polymer support material provided in step a has a nitrogen adsorption capacity of 80 to 1000 m 2 / g, preferably 100 to 800m 2 / g, even more preferably 200 to 600 m 2 The specific surface area is 200 μm / g. The measurement is performed as described in Example 5 below. A high specific surface area increases the capacity and resolving power of the column, especially when separating small ions such as standard ions.

[0079] Another aspect of the invention relates to a modified polymeric support material as described above, wherein the polymeric support material provided in step a has a pressure stability of at most 220 bar, preferably at most 250 bar. By pressure stability, it is understood that the pressure increase as a function of the flow rate behaves only linearly. The measurement is performed as described in Example 6 below. The high pressure stability is produced by the small particle size and the micro / mesoporosis of the particle structure.

[0080] Preferably, the modified polymeric support material is present as particles, preferably as spherical particles, more preferably as spherical particles with an average particle size (median) of 1 to 50 μm. Particularly preferably, the particles are present in a size range of 2 to 25 μm and very particularly preferably in a size range of 3 to 9 μm. In this case, the particle size is the average value between the longest and shortest straight line through the center of the particle, measurable by means of a scanning electron microscope (SEM) and automatic image evaluation.

[0081] The size of the particles can be adjusted by suitable stirring speed, choice of solvent, concentration of polymer in solvent, etc. Methods are known to the skilled person. The carrier polymer of this shape and size has a volume / surface area ratio that has been found to be particularly favorable for exchange capacity. It exhibits high diffusivity into the pores and is easily packable.

[0082] One aspect of the present invention relates to a modified polymer support material as described above, wherein the modified polymer support material is stable in the pH range of 0 to 14. pH stable is understood here to mean that the retention time of sulfate in a column loaded with the modified polymer support material after flushing with 1M NaOH solution and / or flushing with 1M HCl solution deviates by no more than 8%, preferably by no more than 5%, more preferably by no more than 3% from the retention time of sulfate in a column loaded with the modified polymer support material which has not been previously exposed to pH values ​​of 0 and / or 14. The measuring method for pH stability results from the following embodiment example 8.

[0083] Another aspect of the present invention relates to an ion exchange chromatography column packed with a modified polymeric support material, preferably microparticles of modified polymeric support material, which is preparable by the method according to the present invention.

[0084] Furthermore, the invention relates to a method for the chromatographic separation of analytes, characterized in that a solution containing the analyte is brought into contact with the modified polymeric support material according to the invention, in particular by passing it through an ion exchange chromatography column according to the invention.

[0085] The invention also relates to the use of the polymeric support material obtainable by the process according to the invention for the analytical or preparative separation of analytes, in particular for anion exchange chromatography, cation exchange chromatography and / or HILIC chromatography (hydrophilic interaction liquid chromatography).

[0086] To further illustrate the present invention, the following exemplary embodiments are described. The exemplary embodiments do not limit the disclosure and claims of the present invention.

[0087] It shows the following figures:

[0088] Figure 1 : Schematic diagram of an exemplary modification sequence on a polymer support material;

[0089] Figure 2 : Schematic diagram of modification steps b.1 and b.2;

[0090] Figure 3 : Schematic representation of modification steps b.1 and b.2, followed by exemplary modification steps c and d.1;

[0091] Figure 4 : Schematic diagram of alternative modification steps c or d.2;

[0092] Figure 5 : Schematic diagram of the result of modification step d.1, subsequent reaction with BDGE (butanediol diglycidyl ether);

[0093] Figure 6 : Schematic diagram of an embodiment of the modification step e after step c or d.2, introducing ion exchange groups;

[0094] Figure 7 : A chromatogram obtainable using a chromatographic column according to Embodiment 1 or 4;

[0095] Figure 8 : A chromatogram obtainable with the chromatographic column according to embodiment example 1 or 4 with an increased number of repetitions of modification step d;

[0096] Fig. 9 : Pressure-flow curve measured on the chromatographic column according to the present invention;

[0097] Fig.10 : Chromatogram obtainable with a chromatography column according to embodiment example 1 or 4 with increased duration of step f;

[0098] Fig.11 : Pressure-flow curve from method step b.2 measured on a chromatography column packed with the polymer support material according to the invention;

[0099] Fig.12 : Results of particle size analysis by SEM (number vs. diameter [μm]).

[0100] Embodiment 1:

[0101] All substances used were classified as "pure" or "pa" (except hydrogen peroxide and formic acid), and the solvents were separated from the less volatile components by distillation on a rotary evaporator.

[0102] Oxidation with potassium permanganate

[0103] 10.0 g of PS / DVB (55% DVB in EVB) was placed in a 350 mL sulfating flask and suspended with 100 mL of acetonitrile. Then 5.0 g of KMnO4 dissolved in 100 mL of water was added over 20 minutes. The reaction solution was adjusted to an acidic pH with a small amount of acid. The suspension was stirred at 25° C. for 120 h. The particles were treated with semi-concentrated hydrochloric acid and subsequently washed with ultrapure water. The product was dried to constant weight in a vacuum drying oven. The final weight was 9.7 g.

[0104] Reduction with lithium aluminum hydride

[0105] 8.6 g of dry, oxidized particles were placed in a 500 mL reactor and mixed with 150 mL of THF. Under an argon atmosphere and external cooling to 5 ° C, 1.5 g of lithium aluminum hydride was slowly added and mixed with another 50 mL of THF. The reactor was warmed to room temperature and stirred for 17 h. The reaction was stopped. The reaction was stopped by slowly adding water. Subsequently, it was treated with water / acetone, acidified with dilute sulfuric acid and neutrally washed with water. After finally washing with acetone, the solid obtained was dried in a vacuum drying oven. 8.35 g of particles were obtained.

[0106] Reaction with epichlorohydrin (ECH)

[0107] 7.6g of reduced, dried particles are placed in a 250mL three-necked flask. 35mL of epichlorohydrin is added, and the mixture is pumped 3 times and inflated with argon. The solution is heated to 45°C. Subsequently, 7mL of phase transfer catalyst solution (3g tetrabutylammonium hydroxide in 10mL water) is added, and 140mL of sodium hydroxide solution is further added. The reaction is stirred for 3.5 hours, and then stopped by adding water / ethanol. Water / ethanol or water / acetone is used for processing. The product is directly used in the next step without drying.

[0108] Reaction with butanediol

[0109] The above polymer was then suspended in 70 mL of butanediol together with 1.98 g of KOH at room temperature, and then stirred at 130 ° C for 18 h. The reaction mixture was then allowed to react for a few minutes. After the reaction time was over, water was added to the reaction mixture and filtered. The polymer was washed with water and acetone several times. The filter cake was dried overnight in a vacuum drying oven. 7 g of polymer was obtained.

[0110] Attaching spacer

[0111] 6.6 g of the above polymer was suspended in 16.5 mL DMSO and 16.5 mL butanediol diglycidyl ether, and pumped three times, followed by aeration. Then, 1.4 mL of 1 M tetrabutylammonium bromide solution and 16.5 mL of 0.6 M NaOH (aqueous solution) were added, and mechanically stirred for 22 h. The reaction was terminated by adding a solvent. The reaction was terminated by adding a 1:1 mixture of water and ethanol. Repeated washing was performed with a water / ethanol mixture. Finally, the product was filtered to dryness. The polymer was used directly in the next step.

[0112] Introduction of anion exchange groups

[0113] The above polymer is then suspended in 45mL of DMSO without conversion, and 45mL of water is subsequently added. The suspension is heated to 70°C and 45mL of N-methylpyrrolidine is added. After the reaction time of 2h is completed, the reaction is stopped by adding acetic acid. The polymer is filtered out and washed with water several times. The wet polymer is directly used in the next step.

[0114] eliminate

[0115] The above polymer was suspended in 50 mL of water and 7.5 mL of 40% NaOH (aqueous solution) was added. The suspension was then stirred at 100 ° C for 4 h. The reaction was stopped by filtration. The filter cake was washed several times with ultrapure water and then loaded into a 4×100 mm PEEK column according to a known high pressure packing procedure.

[0116] Embodiment 2:

[0117] Oxidation with low pressure oxygen plasma

[0118] 40 g of PS / DVB (55% DVB in EVB) were oxidized in a plasma powder apparatus using an oxygen plasma. The granules can be further processed directly after treatment.

[0119] Reduction with lithium aluminum hydride (LAH)

[0120] In a 1000 mL reactor with pressure equalization, 30 g of the oxidized, dried polymer was suspended in 250 mL of dry ether. Temper to 25° C., slowly add 6 g of lithium aluminum hydride under argon atmosphere, heat to 30° C. for 6 h with stirring, and stir for another 20 h at room temperature. The reaction was stopped by cooling the reaction mixture to 0° C. and slowly adding 15 mL of ethyl acetate. Work up with water, dilute sulfuric acid, water, 5 wt % NaOH solution, ultrapure water and dilute hydrochloric acid.

[0121] The polymer was neutralized and washed with ultrapure water and filtered and dried with acetone.

[0122] The product was dried in a vacuum oven to obtain 30 g of polymer.

[0123] Reaction with epichlorohydrin

[0124] 5.0 g of reduced, dried particles are placed in a 250 mL three-necked flask and 25 mL of epichlorohydrin is added. The suspension is drained 3 times and inflated with argon. Subsequently, 1.75 mL of a 1 M phase transfer catalyst solution (tetrabutylammonium bromide in water) and 25 mL of a 30% sodium hydroxide solution are added, heated to 45 ° C and stirred for 3.5 hours. The reaction is terminated by adding water / ethanol. The product is purified by washing with water / ethanol or water / acetone several times. The product is used directly in the next step without drying.

[0125] Reaction with butanediol

[0126] The above polymer was then suspended in 50 mL of butanediol with 1.3 g of KOH at room temperature and heated to 130° C. for 18 h. The reaction mixture was then allowed to settle. After the reaction time was over, 200 mL of water was added to the reaction mixture and filtered.

[0127] The filter cake was washed with water and acetone. The product was dried in a vacuum oven to obtain 4.2 g of dry product.

[0128] Attaching spacer

[0129] The above polymer of 3.8g is suspended in 10mL of DMSO and 10mL of butanediol diglycidyl ether, and it is subjected to pressure circulation three times, and the reaction vessel is backfilled with argon.Then, 0.8mL of 1M tetrabutylammonium bromide solution and 10mL of 0.6M NaOH (aqueous solution) are added, and stirred for 22h.Then the reaction mixture is subjected to three pressure changes. Subsequently, 200mL of water and 1:1 mixture of ethanol are added to the reaction mixture and filtered.This washing procedure is repeated several times, and the product is filtered to dryness and directly used in the next step.

[0130] Introduction of ion exchange groups

[0131] The above polymer was suspended in 30 mL of DMSO, 30 mL of water was added and the suspension was heated to 70°C. After reaching the reaction temperature, 30 mL of N-methylpyrrolidine was added and stirred at 70°C for 2 h. After the reaction time was over, 60 mL of concentrated acetic acid was added and the product was filtered out. The filter cake was neutrally washed with water and used in elimination.

[0132] eliminate

[0133] The above polymer was suspended in 100 mL of water, mixed with 20 mL of 30% NaOH (aqueous solution) and stirred for 28 h at 100° C. After the reaction time was over, the reaction was stopped by adding hydrochloric acid, the suspension was filtered, the filter cake was neutrally washed several times with water, and then packed into a 4×100 mm PEEK column according to known high pressure packing procedures.

[0134] Embodiment 3:

[0135] Oxidation with m-chloroperbenzoic acid

[0136] 20 g of PS / DVB (55% DVB in EVB) was placed in a 250 mL glass bottle with a screw cap and suspended with 93 g of dichloromethane. Then, 5.5 g of solid meta-chloroperbenzoic acid was added and the reaction mixture was mixed on an oscillator at room temperature for 18 h. The product was washed several times with ethanol and water and dried in a vacuum drying oven to a consistent weight. The final weight was 19.0 g.

[0137] Hydrolysis with hydrochloric acid

[0138] 19 g of the oxidized, dried polymer was placed in a 250 mL glass bottle with a screw cap and suspended with 52 g of acetone and 13 g of hydrochloric acid 37%. The reaction mixture was mixed on a circulating air heated oscillator at 40° C. for 21 h. The mixture was then removed from the bottle. The product was neutrally washed with water, then washed several times with water and acetone and dried in a vacuum drying oven to constant weight. The final weight was 18.5 g.

[0139] Reaction with epichlorohydrin

[0140] The hydrolyzed, dried polymer of 11.8g is suspended in a 250mL three-necked flask containing 60mL of epichlorohydrin. The reaction vessel is subjected to three vacuum / argon cycles. The reaction mixture is heated to 45°C under agitation, and then 3mL of 1M (aqueous solution) tetrabutylammonium bromide solution is added. Subsequently, 60mL of 30% (aqueous solution) sodium hydroxide solution is added and stirred vigorously. After reaction 22h, the reaction mixture is diluted with 200mL of water and 200mL of ethanol, and then the polymer is filtered out. The polymer is washed with acetone, water, and then washed with acetone again.

[0141] Reaction with butanediol

[0142] 5 g of the above product was suspended in a 100 mL three-necked flask with 1.4 g of potassium hydroxide and 50 mL of 1,4-butanediol and mixed at 130 ° C for 19 h. Subsequently, the reaction mixture was cooled and mixed with 45 mL of water. The product was filtered out and washed with water to neutrality, and then dried in a vacuum drying oven to a consistent weight. The final weight was 4.0 g.

[0143] Reaction with 1,4-butanediol diglycidyl ether

[0144] 3.1g of the above product is suspended in a 100mL three-necked flask containing 8mL of dimethyl sulfoxide and 8mL of 1,4-butanediol diglycidyl ether. The reaction vessel is subjected to three vacuum / argon cycles. Under agitation, 0.8mL of 1M (aqueous solution) tetrabutylammonium bromide solution and 8mL of 0.6M sodium hydroxide solution are added to the reaction. After 22h of reaction, 25mL of water and 25mL of ethanol are added to the reaction mixture, and then filtered out. The product is washed once with water and ethanol.

[0145] Introduction of ion exchange groups

[0146] The above product was suspended in a 100 mL three-necked flask with 15 mL of dimethyl sulfoxide, 15 mL of water and 15 mL of N-methylpyrrolidine. The reaction mixture was stirred at 70°C for one hour, then cooled and 30 mL of acetic acid was added. The polymer was filtered off and washed with water.

[0147] eliminate

[0148] The above product was suspended in 50 mL of water and 7.5 mL of 40% (aqueous) sodium hydroxide solution in a 100 mL round-bottom flask and heated to 100° C. After 4 h of reaction, the reaction mixture was cooled and filtered off. The product was washed twice with water and then loaded into a 4×100 mm PEEK column according to a known high pressure loading procedure.

[0149] Embodiment 4:

[0150] Oxidation with formic acid

[0151] 25.0g PS / DVB (55% DVB in EVB) is suspended in 188mL formic acid in a 500mL 3-neck flask with pressure equalization. 54mL of 35% hydrogen peroxide is slowly added via a dropping funnel, and the reaction solution is externally cooled. After the reaction heat has dissipated, stir at room temperature for 65h. After the reaction time ends, the reaction mixture is washed with ultrapure water to no acid, and then dried to constant weight in a vacuum drying oven. The final weight is 27.78g.

[0152] Reduction with lithium aluminum hydride

[0153] 27.64 g of the oxidized, dried polymer was suspended in 270 mL of dry ether in a 500 mL pressurized 3-necked flask, cooled to 0° C. with an ice bath, and 8.8 g of lithium aluminum hydride were carefully added under stirring. After the addition was complete, the ice bath was removed and the reaction mixture was refluxed under stirring for 10 h and stirred for another 24 h at room temperature. The reaction was terminated by external cooling and the addition of ether, ethyl acetate and ultrapure water.

[0154] After the remaining hydride reacts, the reaction mixture is placed on ice and diluted frozen sulfuric acid is added under stirring. The reaction mixture is washed with the following solution: water, 5% NaOH solution, water, diluted acetic acid, water and acetone. The filter cake is filtered to dryness and dried in a drying oven. The yield is 26.20 g.

[0155] Reaction with epichlorohydrin

[0156] 4.00 g of the polymer was suspended in 20 mL each of ECH and DMSO, sonicated in an ultrasonic bath for 15 min, and then subjected to two pressure changes, backfilling the reaction vessel with argon. After adding 4.30 mL of a 25% solution of tetramethylammonium hydroxide in water, stirring was carried out at room temperature for 2 h. The reaction mixture was filtered and washed with a 1:1 mixture of water and 2-propanol and acetone. The filter cake was filtered to dryness.

[0157] Reaction with butanediol

[0158] The above polymer was then suspended in 40 mL of butanediol together with 1.12 g of KOH at room temperature and then stirred at 120 ° C for 20 h. The reaction mixture was washed with water and acetone several times. After the reaction time was over, the reaction mixture was washed with water and acetone several times. The product was filtered to dryness. The wet mass was 13.36 g.

[0159] Coating cycle: reaction with epichlorohydrin (ECH)

[0160] The still wet polymer from the above step was made up to 13.50 g with water, and 1 mL of 1 M tetrabutylammonium bromide and 20 mL of ECH were added. Subsequently, 10.5 mL of 50% NaOH (aqueous solution) was added and stirred for 5.5 h. The reaction mixture was then washed with a 1:1 mixture of water and 2-propanol and acetone. The filter cake was filtered to dryness.

[0161] Coating cycle: reaction with butanediol

[0162] The above polymer was suspended in 40 mL of butanediol together with 1.12 g of KOH at room temperature and then stirred at 120 ° C for 18 h. The reaction mixture was washed with water and acetone several times. After the reaction time was over, the reaction mixture was washed with water and acetone several times. The product was filtered to dryness. The polymer was finally dried and then further reacted. The yield was 5.66 g.

[0163] Attaching spacer

[0164] 2.30g of the above polymer suspension is in 6mL of DMSO and 6mL of butanediol diglycidyl ether, and it is subjected to pressure circulation three times, and the reaction vessel is backfilled with argon. Under agitation, 0.5mL of 1M tetrabutylammonium bromide solution and 6mL of 0.6M NaOH (aqueous solution) are added, and stirred for 22h. Then the reaction mixture is subjected to three pressure changes. Then the reaction mixture is washed with a 1:1 mixture of water and 2-propyl alcohol and filtered to dryness.

[0165] Introduction of anion exchange groups

[0166] The above polymer was suspended in 5 mL DMSO and mixed with 5 mL water and 5 mL N-methylpyrrolidine. Subsequently, the reaction mixture was stirred at 70 ° C for 1 h. The reaction was stopped by adding water and dilute acetic acid. The filter cake was then washed with dilute hydrochloric acid, water and acetone. The obtained polymer was dried in a drying oven at 60 ° C. The yield was 2.54 g.

[0167] eliminate

[0168] The above polymer was suspended in 50 mL of water, 5 mL of 30% NaOH (aqueous solution) was added and stirred at 100 ° C for 2 h. The reaction was terminated by filtration, followed by washing with water, dilute HCl, water and acetone. The filter cake was filtered to dryness, and the polymer was then dried in a drying oven at 60 ° C. No significant weight loss was observed.

[0169] Figure 1 Different, exemplary modification sequences on a core polymer support material (pDVB) are schematically shown. After an initial oxidation (b.1) and subsequent reduction (alternatively: subsequent hydrolysis, b.2), a polymer support material (pDVB-OH) having hydroxyl groups on the surface can be obtained. The polymer support material (pDVB-OH) having OH groups can then be reacted with epichlorohydrin (ECH). This produces a compound according to step c. Alternatively, the polymer support material (pDVB-OH) comprising OH groups can be reacted with butanediol diglycidyl ether (BDGE) in step c.

[0170] According to the invention, the polymer support material can be reacted with ECH, diols in one or more coating cycles after step b.2 and subsequently with ECH or BDGE again (steps c, d.1, d.2). It is also possible to react the polymer support material directly with BDGE, for example after step b.2. The result is a modified polymer support material with suitable reactive functional groups on the surface. In the illustrated embodiment, these are epoxy groups.

[0171] In principle, any combination of ECH / BDGE modification in steps c and d.2, respectively, and any combination of diol conversion / hydrolysis in step d.1 is conceivable. However, as described above, it is preferred if the spacer molecule is inserted during the last coating cycle in d.2.

[0172] Figure 1 The modified polymer support material shown in is suitable for subsequently introducing ion exchange groups. The oxygen content at the surface of the modified polymer support material increases with the order of the variants listed in the previous part (variants from top to bottom in the figure). When ion exchange groups are introduced in each product, the result is an ion exchange material whose hydrophilicity increases with the order of the listed variants. The hydrophilicity that increases itself shows, for example, a selectivity σ from NO to the reduction of Cl.

[0173] Figures 2 to 6 The method steps according to the invention are intended to be illustrated and the reaction sequences are shown in highly simplified form. They are not required to be complete. The focus is on the respective modification on the surface of the polymer support material. The parts of the unmodified polymer support material in the respective steps are shown in simplified form as spherical particles.

[0174] Figure 2 Modification steps b.1 and b.2 are schematically shown. After oxidation and reduction (alternatively: hydrolysis), a polymer support material with OH groups on the surface is provided. It is known to the skilled person that not only ketones can be formed in the oxidation step. Depending on the treatment and in particular during the treatment with KMnO4, in addition to ketones, diols, diketones or dicarboxylic acids as cleavage products can also be formed. Such methods and intermediates are covered by the claimed method and are not intended to be excluded by the embodiments shown in the figures.

[0175] Figure 3 Modification steps b.1 and b.2 are schematically shown, followed by exemplary modification steps c and d.1. In the variant shown, the compound having at least one first functional group reactive with hydroxyl groups and at least one second functional group reactive with amines and / or hydroxyl groups used in step c is epichlorohydrin. In the embodiment shown, the polyfunctional compound containing hydroxyl groups used in step d.1 is butanediol. The coating sequence consisting of alternating reactions with epichlorohydrin and butanediol can be repeated as in d.1 and d.2. The resulting particles are again abstractly shown after the double arrow.

[0176] Figure 4 An alternative modification step c or d.2 is schematically shown. The compound having at least one first functional group reactive with hydroxyl groups and at least one second functional group reactive with ion exchange groups and / or hydroxyl groups used in step c or d.2 is BDGE.

[0177] One or more coating cycles can also be accomplished using BDGE conversion, such as Figure 3 As shown in . Figure 5 The result of modification step d.1 is shown schematically and exemplarily. After using ECH in step c, a coating cycle is performed using ECH in step d.2. After reaction with butanediol, BDGE is then used as a spacer for the final step d.2. The result is a 20% saturation product having a saturation of 1.0% saturation product. Figure 3 / Figure 4 The method provides a modified polymer support material with a higher surface oxygen content in the obtained support material.

[0178] Figure 6 The modification step e after step c or d.2 is schematically shown, an embodiment of introducing ion exchange groups. In the embodiment shown, the ion exchange groups are formed by quaternization of 1-methylpyrrolidine. After modification according to the present invention, a polymer support material with side chains on the surface is obtained, such as those shown in the embodiments.

[0179] Figure 7 The chromatograms obtainable with the chromatographic columns according to Example 1 or 4 are shown. The x-axis shows the run time in minutes. The y-axis shows the conductivity in μS / cm. For this purpose, the dried substrate is loaded into a 150×4 mm column. The eluents used are 6.0 mmol / L Na2CO3 and 1.0 mmol / L NaHCO3. The analytes of the standard solution present mutually separated baselines, wherein the elution order from left to right is fluoride, bromate, chloride, nitrite, bromide, chlorate, nitrate, azide, phosphate, sulfate. Bromate can be quantitatively present before chloride (peaks at 5.2, 5.7 min run time), and the chromatogram gives high signal symmetry. The total run time of the column is as short as 15 min. The chromatographic column prepared under the conditions of Example 1 provides a similar chromatogram.

[0180] Figure 8Three chromatograms obtained with the chromatographic column according to Example 4 are shown. Example 1 provides very similar chromatograms. The X-axis shows the running time in minutes. The y-axis shows the conductivity in μS / cm. The curve shows the chromatogram of the same standard solution, in which the elution order from left to right is fluoride, chloride, nitrite, bromide, nitrate, phosphate and sulfate. The number of repetitions of the modification step d.1 / d.2 increases (from top to bottom). For the plotted curve A, the step sequence d.1 / d.2 is performed once. For the point curve B, the step sequence d.1 / d.2 is performed twice. For the dashed curve C, the step sequence d.1 / d.2 is performed three times. Therefore, specifically, in the case of the plotted curve A, a polymer substrate subjected to oxidation / reduction treatment, treated once with ECH and then treated once with 1,4-butanediol and then reacted with BDGE is used. In curve B, a polymer substrate is used that has been subjected to an oxidation / reduction treatment, treated with ECH and then treated with 1,4-butanediol, then treated with ECH again and then treated with 1,4-butanediol, and then reacted with BDGE. Curve C shows a polymer substrate subjected to an oxidation / reduction treatment. Thereafter, the following sequence of steps occurs: reaction with ECH; reaction with 1,4-butanediol; reaction with ECH; reaction with 1,4-butanediol; reaction with ECH; reaction with 1,4-butanediol; reaction with BDGE. In all three cases, the modified substrate is then reacted with methylpyrrolidine. It is clear from the chromatogram that the signals of the anions affected by tailing (nitrite, bromide, nitrate) gain symmetry with increasing number of coating cycles. The selectivity σ of NO3 to Cl decreases with increasing number of plating cycles. The total capacity decreases.

[0181] Fig. 9 The pressure-flow curve measured at room temperature on a chromatographic column according to the invention prepared according to Example 4 is shown. The y-axis shows the system pressure in MPa. The x-axis shows the flow rate in mL / min. Seventeen intervals of 20 minutes were measured while the flow rate was gradually increased from 1 mL / min to 2.6 mL / min. The pressure depends linearly on the flow rate. This is in contrast to the results obtained with conventional columns packed with a hydrophilic pDVB substrate. For conventional columns, the pressure increases more than linearly as a function of the flow rate. For example, a hyperbolic slope of the function can be obtained.

[0182] Fig.10The chromatograms obtainable with a chromatographic column according to the present invention, in particular with a chromatographic column filled with a modified polymer support material according to Example 1 or 4 are shown. The x-axis shows the run time in minutes. The y-axis shows the conductivity in μS / cm. The duration of step f is different. The dried substrate is loaded into a 100×4 mm column. In each case, the curve shows a chromatogram of the same standard solution, wherein the elution order from left to right is fluoride, chloride, nitrite, bromide, nitrate, phosphate, and sulfate. From top to bottom, the curve shows the chromatograms obtainable after eliminating the column substrate in step f during 0 min (A), 60 min (B), 120 min (C), 180 min (D), 240 min (E) and 300 min (F). When step f (0 min) is omitted, the nitrate peak and the phosphate peak overlap. The total capacity decreases with a longer elimination time. The analytes present baselines separated from each other and the chromatogram provides high signal symmetry. The total column run time is as short as approximately 14 to 20 minutes.

[0183] Example 5: Determination of the average pore radius and specific surface area of ​​the polymer support material provided in step a.

[0184] In Example 1, the modification according to the invention was carried out on PS / DVB (55% DVB in EVB). The starting polymer support material provided is therefore hydrophobic and microporous or mesoporous. The starting polymer support material provided is obtained as follows:

[0185] Polystyrene seed particles were prepared in a dispersion polymerization of styrene in ethanol stabilized with polyvinylpyrrolidone and initiated with azobisisobutyronitrile. N =15kg / mol, M W =55 kg / mol polystyrene particles. The obtained polystyrene particles were swollen in an emulsion of 55% divinylbenzene (DVB) / 45% ethylvinylbenzene (EVB) and toluene in water / isoamyl alcohol, stabilized with polyvinyl alcohol and subsequently polymerized by azobisisobutyronitrile. 3 Porous, highly cross-linked poly(DVB-co-EVB) particles with a porosity of 1000 Å / g.

[0186] The average pore radius of the starting polymer support material was determined by nitrogen adsorption in the BJH (Barret, Joyner, Halenda) model. The specific surface area was determined by nitrogen adsorption in the BET model (Brunauer, Emmett, Teller). A sample of 0.0945g of PS / DVB polymer support material was used for both analyses. The density of the sample material is 1.05g / cc. The measurements were performed in a 9mm chamber on an Autosorb iQ S / N:14713051301 instrument. The bath temperature was 77.35K. The final degassing temperature was 60°C. The measurements were evaluated on Quantachrome ASiQwin version 3.01. The measurements were performed twice, once with an immersion time of 80min and once with an immersion time of 40min. The degassing rates were 1.0°C / min and 20.0°C / min, respectively. The average pore radius obtained by the BJH method based on pore volume is 5.060nm. The specific surface area calculated from the multi-point BET diagram is 815.0m 2 / g.

[0187] Example 6: Determination of the compression stability of the polymer support material according to step b.2

[0188] In Example 4, the modification according to the invention was carried out on PS / DVB (55% DVB in EVB). The starting polymer support material provided was obtained as described in Example 5. According to the results of step b.2, oxidation with hydrogen peroxide and reduction with lithium aluminum hydride were carried out on the starting polymer support material, both as described in Example 4. The obtained particles were subjected to compression tests. For the pressure test, a 250×4 mm column was filled with the obtained particles and water was passed through the column at an increasing flow rate. Fig.11 The pressure-flow curve measured at room temperature is shown. The y-axis shows the system pressure in bar. The x-axis shows the flow rate in mL / min. Eight intervals of 30 seconds were measured, with the flow rate increasing stepwise from 0.2 mL / min to 1.6 mL / min. As can be seen from the figure, the pressure depends linearly on the flow rate up to a pressure of 400 bar or 40 MPa.

[0189] Example 7: Determination of average particle size

[0190] Determine the roundness and average particle size of a sample of the starting polymer support material provided in step a. The sample is sputtered onto a scanning electron microscope slide as a single particle layer. For this purpose, the sample is deposited on a scanning electron microscope slide as a single particle layer and coated with gold using a LOTAutomaticSputterCoaterMSC1 sputter coater connected to a Vacubrand RZ 6 vacuum pump. A series of 27 images are acquired using a scanning electron microscope (Phenom ProX), and individual particles are identified and measured using Olympus imaging solution scandium. The spherical diameter and roundness of the identified particles are analyzed. All images are analyzed in a batch using the same threshold and measurement settings. A total of 6039 particles were measured, and their roundness was always ≥0.8. The measurement results are shown in Figure 2. Fig.12 It is shown in . It shows that the y-axis is the number of particles and the x-axis is the diameter in μm. The minimum measured radius is 0.8 μm and the maximum is up to 10 μm. The average diameter (median) is 4.59 μm with a relative standard deviation of 6.23%. The polydispersity index PDI (Mw / Mn) is 1.044.

[0191] Example 8: Determination of pH stability

[0192] The pH stability of a sample of the particulate polymer support material according to Application Example 5, which was modified according to Example 4, i.e. corresponds to the polymer material obtainable according to steps a to f, was determined. For this purpose, the sample was loaded into a chromatographic column (250×4 mm) and the retention time of the sulfate was determined by ten measurements with an eluent of 6 mmol / L Na2CO3 and 1 mmol / L NaHCO3. Subsequently, the column was flushed with an eluent of 6 mmol / L Na2CO3 and 1 mol / L NaOH (pH 14) at 0.8 mL / min for 14 h. Then, the retention time of the sulfate was measured again 10 times with an eluent of 6 mmol / L Na2CO3 and 1 mmol / L NaHCO3. Subsequently, the column was flushed with an eluent consisting of 6 mmol / L Na2CO3 and 1 mol / L HNO3 (pH 0) at 0.8 mL / min for 14 h. Then, the retention time of the sulfate was measured again 10 times with an eluent of 6 mmol / L Na2CO3 and 1 mmol / L NaHCO3. Each time the eluent was changed, washing with water was performed for 1 h to avoid precipitation.Possible variations were investigated based on retention time and plate number of sulfate; both parameters deviated by a maximum of 3% from the parameters initially determined after both alkaline and acidic treatments.

Claims

1. A method for modifying a polymer support material used as a stationary phase in an analytical or preparative separation method, comprising the following steps a. providing a polymer support material, the polymer support material being at least partially formed from an aromatic hydrocarbon compound having at least two vinyl or allyl substituents; b. generating hydroxyl groups on / in the polymer support material by a method comprising the following steps b.1 Oxidative treatment of the polymer support material, and subsequently b.2 Reduction treatment or hydrolysis treatment of the reaction product of step b.1; c. Optionally: reacting the product of step b.2 with a polyfunctional compound.

2. The method according to claim 1, characterized in that The polymeric support material is formed at least in part from divinylbenzene monomers.

3. The method according to claim 1, characterized in that The multifunctional compound comprises at least one first functional group reactive with a hydroxyl group and at least one second functional group reactive with an amine and / or a hydroxyl group.

4. The method according to claim 3, characterized in that The first functional group is a halogen group.

5. The method according to claim 3, characterized in that: The second functional group is an epoxy group.

6. The method according to claim 3, comprising steps a, b and c, wherein step c is followed by step d: d. Carry out a coating cycle comprising the following steps d.1 The second functional group introduced in step c is reacted to introduce or generate a hydroxyl group by the following reaction: - react with a polyfunctional compound having a hydroxyl group, or - hydrolysis, or - their combination; d.2 reacting the product of step d.1 with a multifunctional compound; The number of coating cycles is 1 to 20.

7. The method according to claim 6, characterized in that The multifunctional compound having a hydroxyl group is a polyol.

8. The method according to any one of claims 6 to 7, further comprising the steps of: e. Introducing ion exchange groups on the reaction product from step c or d.

2.

9. The method according to any one of claims 1 to 7, characterized in that The polymer support material in step a, which is at least partially formed from an aromatic hydrocarbon compound having at least two vinyl or allyl substituents, is further partially formed from a monomer selected from the group consisting of -ethylvinylbenzene, - vinyl acetate, - styrene, and - their combination; The proportion of aromatic hydrocarbon compounds having at least two vinyl or allyl substituents is at least 50% by weight.

10. The method according to any one of claims 1 to 7, characterized in that The polymer support material in step a, which is at least partially formed from divinylbenzene monomers, is further partially formed from monomers selected from -ethylvinylbenzene, - vinyl acetate, - styrene, and - their combination; The proportion of divinylbenzene is at least 50% by weight.

11. The method according to any one of claims 1 to 7, characterized in that The oxidation treatment in step b.1 is treatment with peracid, treatment with KMnO4, treatment with oxygen plasma or a combination thereof.

12. The method according to claim 11, characterized in that The peracid is selected from the group consisting of meta-chloroperbenzoic acid, performic acid, peracetic acid and peroxytrifluoroacetic acid.

13. The method according to any one of claims 3 to 7, characterized in that The polyfunctional compound used in step c comprising at least one first functional group reactive with a hydroxyl group and at least one second functional group reactive with an amine and / or a hydroxyl group is an epihalohydrin.

14. The method according to claim 13, characterized in that The epihalohydrin is epichlorohydrin.

15. The method according to any one of claims 3 to 7, wherein the multifunctional compound used in step c comprising at least one first functional group reactive with a hydroxyl group and at least one second functional group reactive with an amine and / or a hydroxyl group is a spacer molecule.

16. The method according to claim 15, characterized in that The spacer molecule is a diepoxide.

17. The method according to claim 15, characterized in that The spacer molecule is butanediol diglycidyl ether.

18. The method according to claim 6 or 7, characterized in that: The polyfunctional compound comprising at least one first functional group reactive with a hydroxyl group and at least one second functional group reactive with an amine and / or a hydroxyl group used in step d.2 is an epihalohydrin or a spacer molecule.

19. The method according to claim 6 or 7, characterized in that: The number of coating cycles was 1 to 10.

20. The method according to claim 19, characterized in that The number of coating cycles was 1 to 5.

21. The method according to claim 20, characterized in that The number of coating cycles was 1 to 3.

22. The method according to claim 8, characterized in that The ion exchange groups are introduced by reacting the reaction product of step c or d.2 with a compound of an organic element of the 5th main group.

23. The method according to claim 22, characterized in that The organic element compound of the fifth main group is an amine.

24. The method according to claim 23, characterized in that The amine is a tertiary amine.

25. The method according to claim 8, characterized in that Step e is followed by step f which comprises heating said polymer support material provided with ion exchange groups in an alkaline solution.

26. A modified polymeric support material obtainable by a process according to any one of claims 1 to 25 for use as a stationary phase in an analytical or preparative separation process.

27. The modified polymer carrier material according to claim 26, characterized in that The analytical or preparative separation method is a chromatographic method.

28. A modified polymer support material obtained by the process according to any one of claims 1 to 25 for use as a stationary phase in an analytical or preparative separation process, The polymer support material provided in step a is hydrophobic and microporous or mesoporous.

29. The modified polymer carrier material according to claim 28, characterized in that The analytical or preparative separation method is a chromatographic method.

30. The modified polymeric support material according to claim 26 or 28, wherein the polymeric support material provided in step a is additionally partially composed of monomeric units selected from the group consisting of: - monomer units derived from ethylvinylbenzene; - monomer units derived from styrene; -A combination of these.

31. The modified polymer carrier material according to claim 26 or 28, wherein the polymer carrier material provided in step a is composed of monomer units selected from the group consisting of: - monomer units derived from divinylbenzene; - monomer units derived from ethylvinylbenzene; - monomer units derived from styrene; -A combination of these.

32. The modified polymer support material according to claim 26, wherein the polymer support material provided in step a. has an average pore radius of 1 to 50 nm measured by nitrogen adsorption in a BJH model.

33. The modified polymer support material according to claim 32, wherein the polymer support material provided in step a. has an average pore radius of 2 to 25 nm measured by nitrogen adsorption in the BJH model.

34. The modified polymer support material according to claim 33, wherein the polymer support material provided in step a. has an average pore radius of 2 to 10 nm measured by nitrogen adsorption in the BJH model.

35. The modified polymer support material according to claim 26, wherein the polymer support material provided in step a. has a nitrogen adsorption capacity of 80 to 1000 m / s as measured by BET model. 2 / g specific surface area.

36. The modified polymer support material according to claim 35, wherein the polymer support material provided in step a. has a nitrogen adsorption capacity of 100 to 800 m / s as measured by the BET model. 2 / g specific surface area.

37. The modified polymer support material according to claim 36, wherein the polymer support material provided in step a. has a nitrogen adsorption capacity of 200 to 600 m / s as measured by the BET model. 2 / g specific surface area.

38. The modified polymer support material according to claim 26, wherein the polymer support material provided according to step b.2 is pressure stable at a pressure of at most 220 bar.

39. The modified polymer support material according to claim 26, wherein the polymer support material provided according to step b.2 is pressure-stable at a pressure of at most 250 bar.

40. The modified polymer support material according to claim 26, wherein the polymer support material provided according to step b.2 is pressure stable at a pressure of at most 300 bar.

41. The modified polymer support material of claim 26, wherein the polymer support material provided in step a is in the form of particles.

42. The modified polymer support material of claim 41, wherein the particles are spherical particles.

43. The modified polymer support material of claim 42, wherein the spherical particles have an average particle size of 1 to 50 μm.

44. The modified polymer support material of claim 43, wherein the spherical particles have an average particle size of 2 to 25 μm.

45. The modified polymer support material of claim 44, wherein the spherical particles have an average particle size of 3 to 9 μm.

46. ​​The modified polymer support material of claim 26, wherein the material is stable in the pH range of 0 to 14.

47. A modified polymer support material according to claim 26, wherein the retention time of sulfate in a column packed with the modified polymer support material after flushing with 1M NaOH solution and / or flushing with 1M HNO3 solution deviates by no more than 8% from the retention time of sulfate in a column packed with the modified polymer support material that has not been previously exposed to a pH value of 0 to 14.

48. A modified polymer support material according to claim 47, wherein the retention time of sulfate in a column packed with the modified polymer support material after flushing with 1M NaOH solution and / or flushing with 1M HNO3 solution deviates by no more than 5% from the retention time of sulfate in a column packed with the modified polymer support material that has not been previously exposed to a pH value of 0 to 14.

49. A modified polymer support material according to claim 48, wherein the retention time of sulfate in a column packed with the modified polymer support material after flushing with 1M NaOH solution and / or flushing with 1M HNO3 solution deviates by no more than 3% from the retention time of sulfate in a column packed with the modified polymer support material that has not been previously exposed to a pH value of 0 to 14.

50. A chromatography column packed with the modified polymeric support material according to any one of claims 26 to 49.

51. The chromatographic column according to claim 50, characterized in that The chromatographic column is an ion exchange chromatographic column.

52. A method for chromatographic separation of analytes, characterized in that A solution containing the analyte is contacted with a modified polymeric support material according to any one of claims 26 to 49.

53. A method for chromatographic separation of analytes, characterized in that Passing a solution containing the analyte through a chromatography column according to claim 50 or 51.

54. Use of a polymeric support material according to any one of claims 26 to 49 or a polymeric support material obtained by a process according to any one of claims 1 to 25 for the analytical or preparative separation of analytes.

55. The use according to claim 54, characterized in that The analytical or preparative separation is selected from anion exchange chromatography, cation exchange chromatography and HILIC chromatography.

Citation Information

Patent Citations

  • Separation material

    EP3248678A1

  • Coated ion exchange substrate and method of forming

    US20050181224A1

  • Covalently bonded coatings

    US5503933A

  • Porous polymer particle, alkali-resistant anion exchanger, producing method thereof, column for ion chromatography, and method for measuring anions

    EP1217012A1